Análisis y diseño de un sistema de administración de pacientes para "La Clínica Maternidad La Primavera" - Martínez San Andrés, Gisela Fernanda (2016)
Before the “Clinica Maternidad La Primavera”, completed the information on paper manually many times for each procedure, it didn’t have the access to the information through a graphical interface, neither in all the machines throughout the Clinic, only in some specific places. The purpose of the actual project is to develop a web platform, which will allow the access to the data from anywhere in the clinic being a cellphone, tablet or computer which has the network interface and in different operating systems, altogether with the development, using freeware tools, of a new database in a graphical environment so it can be friendly to the user, and that the same user can access without any problems and in a transparent form to the platform, and finally develop the processes necessary to implement the system, complaining also to give the security to the data by the use of users and passwords that allow them the access to some sections of the data in the database, so this way its given the solution to the necessities not only present today but also in the future. As a result, it can be seen that the system NewJmedics has achieved the avoidance of redundancy in the information since entering the data directly to the database, almost doesn’t exist the possibility to duplicate the data of a patient, and it has improved the security of the access from each user according to the level assigned and will have access to see only some information or modify it.